Fertilizer requirement of babycorn (Zea mays) in wet and winter seasons - SAHOO, S C; PANDA, M M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out during winter 1995-96 (December-February) and wet (July-August) season 1996 at Jashipur in Orissa to work out the fertilizer requirement of babycorn (Zea mays L.) for increasing its productivity.Treatments consisted of application of 7 levels of N, P, K, viz, N0 P0 K0, N20 P4.4 K8.3, N40 P8.7 K16.7, N60 P12.1 K25, N80 P17.5 K33.3, N100 P21.8 K41.7 and N120 P26.2 K50 kg/ha. Application of N120 P26.2 K50 brought about a significantly higher yield compared with other fertilizer levels, giving 1634 and 1491 kg/ha in winter and wet seasons, with a corresponding net profit of Rs 10300 and Rs 7700/ha respectively.